Tradisi Ngesuki Masyarakat Kecamatan Secanggang Dalam Analisis Kaidah Maqashid Alfadz - Iqbal, M; Harahap, Muhammad Rifai (Al-Sharf: Jurnal Ekonomi Islam, 2023)
In Secanggang sub-district, precisely in Suka Mulia Village, Tanjung Mulia Hamlet, there is a unique tradition carried out by the people which they consider as a form of mutual help. This tradition, known as "ngesuki", occurs by giving basic food ingredients to neighbors or friends who are going to hold a party, with the stipulation that the recipient must return what he received to the giver one day when the giver needs food too. This research was carried out to find out this traditional tathbiq when analyzed from Lafadz's rules in muamalah, and also to find out what the legal implications are, the research approach was carried out with a qualitative approach, the data taken was primary data sourced directly from the community who did it, and also secondary data which is taken from several turats literature. The results of this research show an analysis of the rules of lafaz muamalah that the tradition of mutual help carried out by the Secanggang community is actually a tijarah and not a tabarru' contract, so the legal implications are buying and selling death and buying and selling by bartering, and in practice you have to pay attention to all the rules in buying and selling. then the recipient of the food must return the goods in the same quantity and type as the goods he received.